An explanatory model of suicidal ideation based on family functionality and mental health problems: A cross-sectional study of medical students - Leslie Aguilar-Sigueñas; David Villarreal-Zegarra (Interacciones)
Background: One of the mental health problems with the greatest impact on people's lives is suicidal behavior, a largely preventable public health problem that accounts for almost half of all violent deaths. The aim of the study is to propose a model that can explain and predict suicidal ideation based on mental health problems (stress-anxiety-depression) and family functionality (cohesion, flexibility, and cohesion).